Draft Annual Plan 2011-2012 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2011)
Arunachal Pradesh, a predominantly tribal State, is the largest and youngest State amongst NE States. The State is the sentinel of the North Eastern border of the country. It is located in the North Eastern part of the country with a geographical area of 83743 sq.kms, which is about 2.55% of the total land area of the country and about one third the area (32.83%) of the North-East of the country.
Government of Arunachal Pradesh, Department of Planning